Stimuli‐Responsive SiO2‐graft‐Poly(sodium acrylate) Hybrid Nanoparticles via Cu2+‐Amine Redox‐Initiated Radical Polymerization. Issue 24 (2nd October 2013) - Tao, Feng; Chen, Xiaobo; Zhai, Guangqun
<x xml:space="preserve">Abstract</x> A novel strategy is proposed to initiate radical graft polymerization of sodium acrylate (NaAAc) from amine‐functionalized SiO2 nanoparticles (SiO2‐NH2) to prepare hybrid SiO2 nanoparticles with NaPAAc chains (SiO2‐g‐NaPAAc). The polymerization is carried out in aqueous media at ca. 70–90 °C using CuSO4 as an oxidizing agent. Cu2+ oxidizes primary amine into aminyl radicals, initiating radical graft polymerization of NaAAc. The hybrid SiO2‐g‐NaPAAc nanoparticles are characterized by infrared spectroscopy, thermal gravimetric analysis, and X‐ray photoelectron spectroscopy. The morphology is observed by electron microscopy. NaPAAc chains are successfully grafted from SiO2‐NH2, and the grafting yield is as high as 59.46 wt%. SiO2‐g‐NaPAAc exhibits a lower degree of aggregation compared with SiO2‐NH2 when dispersed in aqueous media. SiO2‐g‐NaPAAc exhibits a more stable dispersion in deionized water than SiO2‐NH2, and addition of a low‐molecular‐weight electrolyte reduced the stability of SiO2‐g‐NaPAAc in aqueous dispersion, due to the pH‐sensitive polyelectrolyte effect of NaPAAc chains. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>